2022
DOI: 10.1002/dep2.198
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer species of Cyanobacteria in hot springs and their role to travertine formation: The case of Aedipsos hot springs, Euboea (Evia), Greece

Abstract: Cyanobacteria are considered to be among the first microorganisms to settle in hot springs where they form a favourable environment for further biological establishment. Nevertheless, the exact pioneer species and how early they start participating in the biomineralisation processes remain unknown. The aim of the present study was twofold, that is, to identify the pioneer Cyanobacteria in hot springs (i.e. Aedipsos area, Greece) and to record their early biomineralisation processes. The in situ experimental ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…schmidlei, and Mastigocladus laminosus had an affinity with high NO 3 -, K + , Na + and SO 4 2and with low pH, T, CI -, and PO 4 3in this study (sampling sites S1A). Similar to this study, Spirulina subtilissima was not related to temperature in Öztürk ( 2021), but contrary to these studies, the taxon was detected at higher temperatures in the study by Kanellopoulos et al (2022). Mastigocladus laminosus, which did not show a positive correlation with temperature and pH in this study, on the contrary, has a positive correlation with the temperature and pH in the study by Singh et al (2018) Arman et al (2014), it was reported that it was determined from 53 °C, 6.86 pH, and 1945mg/L SO 4 2water parameters.…”
Section: Discussionsupporting
confidence: 79%
“…schmidlei, and Mastigocladus laminosus had an affinity with high NO 3 -, K + , Na + and SO 4 2and with low pH, T, CI -, and PO 4 3in this study (sampling sites S1A). Similar to this study, Spirulina subtilissima was not related to temperature in Öztürk ( 2021), but contrary to these studies, the taxon was detected at higher temperatures in the study by Kanellopoulos et al (2022). Mastigocladus laminosus, which did not show a positive correlation with temperature and pH in this study, on the contrary, has a positive correlation with the temperature and pH in the study by Singh et al (2018) Arman et al (2014), it was reported that it was determined from 53 °C, 6.86 pH, and 1945mg/L SO 4 2water parameters.…”
Section: Discussionsupporting
confidence: 79%
“…Apart from finding natural alternatives to antibiotics, this is important both for those patients in which some antibiotics may be toxic-typical examples include allergies [63][64][65], liver toxicity [66][67][68][69], and other side effects [70]-and also, and perhaps more significantly, due to the increasing antibiotic resistance [71][72][73][74][75][76][77]. The rapid increase in antibiotic resistance is mainly explained by the overuse of antibiotics [78][79][80] and the high adaptability of bacteria in general, which may survive, depending on the species, even in extreme environments such as hot springs (e.g., [81][82][83]). The research on the antibacterial properties of capsaicin is extensive (Table 1) and this leaves open many potential choices for new drug design.…”
Section: Antibacterial Properties Of Capsaicinmentioning
confidence: 99%
“…The travertines present a large variety of facies [28,30,31,49] with strong indications of biomineralization processes [28,29]. Recent studies prove the contribution of Cyanobacteria to the formation of travertines [32], even in the very early stages of Cyanobacteria settlement [33].…”
Section: Sample Description and In-situ Analysismentioning
confidence: 99%
“…Previous studies have been conducted in the study of the thermogenic travertine of Northern Euboea (Greece) [28][29][30][31][32][33][34]. The present study is the first attempt to examine the stratification of microbial mats in the hot springs of the Aedipsos area (i.e., biodiversity, mineralogical composition, and biomineralization processes of calcium carbonate minerals taking place at the top layers).…”
Section: Introductionmentioning
confidence: 97%